Development and validation of risk prediction model for venous thromboembolism in postpartum women: multinational cohort study - Sultan, Alyshah Abdul; West, Joe; Grainge, Matthew J.; Riley, Richard D.; Tata, Laila J.; Stephansson, Olof; Fleming, Kate M.; Nelson-Piercy, Catherine; Ludvigsson, Jonas F. (BMJ Publishing Group, 2016)
Objective: To develop and validate a risk prediction model for venous thromboembolism in the first six weeks after delivery (early postpartum).